Mobility Management for Satellite / Terrestrial Multi-Service Convergence Networks - Kwong, Chiew Foong (IEEE, 2009)
Hybrid networks of terrestrial and satellite is seen to be the perfect choice of strategy to support the vision of total global. This will indeed fulfill the connectivity of “anytime”, “anyplace” and “anyone”. The ubiquitous solution were sought to fulfill this vision. However there was a challenge to integrate all existing technology into a single entity, especially the efficiency of the mobility management. This paper will discuss the different strategy in mobility management of terrestrial / satellite convergence network in order to attempt to explain the functionality and discuss the problems involved and proposed solution in order to create a more efficient seamless ubiquitous communication.